On the Optimization of Recirculated Aquaculture Systems - Rodrigues, H.C.; Papáček, Štěpán; Petera, Karel; Herskovits, J.; Masaló, Ingrid; Mota Soares, C.M.; Araújo, A.L.; Oca, Joan; Guedes, J.M.; Folgado, J.O.; Moleiro, F.; Madeira, J.F.A. (Springer Nature Switzerland AG, 2019)
The improved design of recirculated aquaculture systems (RAS) is needed facing the demand for increased fish production as well as increased concern of fish wellbeing. Here, we make a step towards using of computational fluid dynamics (CFD) for the optimization of fish tanks. The proposed CFD based methodology allows the modeler (the designer) to manipulate both the tank geometry and operating conditions, in order to solve a multicriteria optimization problem. The individual objective functions are quantifying multiple criteria, dealing mainly with the rearing conditions for fish (a determined average velocity and low velocity variance), fast biosolids removal and the cost of energy and place. As an example of our methodology, we present a study involving the CFD analysis of four different RAS: (i) the circular, (ii) the octagonal, (iii) the square, and (iv) the rectangular multivortex RAS, either with or without additional plate baffles between two water inlets. Based on the two-dimensional description of the flow field within each RAS configuration, the set of efficient solutions for RAS is inferred.
Keywords: CFD; Recirculated aquaculture systems; Optimization